Dynamic morphology of dilated ascending aorta and its implications for proximal landing during thoracic endovascular aortic repair - Skrypnik, Denis; Bischoff, Moritz; Meisenbacher, Katrin; Hagedorn, Matthias; Kilian, Samuel; Rengier, Fabian; André, Florian; Böckler, Dittmar; Steen, Henning (Journal of endovascular therapy, 2024)
Introduction: To improve the outcomes of thoracic endovascular aortic repair (TEVAR), we investigated the dynamic morphology of dilated and nondilated ascending aortas (AAs) to determine whether an appropriate proximal landing zone for TEVAR exists if the middle AA is dilated. - Materials and Methods: Patients with dilated (diameter 40-50 mm) and nondilated (<40 mm) AAs underwent electrocardiogram-gated computed tomography angiography of the entire AA in the systolic and diastolic phases. For each plane of each AA segment, the maximal and minimal diameters in systole and diastole were recorded. - Results: A total of 105 patients were enrolled (54% male; median age: 80 years [IQR 78-85]). A total of 35 patients were included in the dilated AA group (DG), and 70 patients were included in the nondilated AA group (n-DG). The aortic planes of the AA segment at the sinotubular junction (STJ) showed a more oval-shaped morphology compared with the distal planes of the same segment (the differences between the maximum and minimum diameters were 8.9% to 9.4% and 4.8% to 5.6%, respectively). If the mid-ascending aorta was dilated, the aortic segment at the STJ showed a more pronounced reversed-funnel 3D morphology, with a 14% (IQR 11%-19%) difference in diameters between the proximal and distal segmental planes shown in the n-DG and 18% (IQR 16%-22%, p<0.001) in the DG. - Conclusion: If the middle AA is dilated, it is considered unsuitable to perform TEVAR using conventional endografts without additional proximal fixation in the aortic segment at the STJ due to its pronounced reversed-funnel segmental morphology. By contrast, the aortic segment at the brachiocephalic trunk seems to be promising for performing TEVAR using an endograft of the appropriate size and conformability. Moreover, endograft sizing using the average aortic diameter instead of the maximal AA diameter in an oval-shaped aortic plane morphology should be considered. - Clinical Impact - If the middle ascending aorta is dilated, it is considered unsuitable to perform TEVAR with a proximal landing in the aortic segment at the sinotubular junction due to its pronounced reversed-funnel segmental morphology and high risk of type Ia endoleak and endograft migration. By contrast, the aortic segment at the brachiocephalic trunk seems to be promising for performing TEVAR due to its moderate funnel morphology using an endograft of appropriate size and conformability.